2014
DOI: 10.1007/s11332-014-0192-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of starting conditions in track cycling

Abstract: Purpose Several factors may influence cycling performance and effort intensity during cycling competitions. The present study aimed to investigate the conditions that may influence the initial acceleration during the first 5 m of a cycling competition, particularly riding position, starting angle of the crank and hand position on handlebars. To this aim, eight male cyclists amateur were tested in laboratory and on track. Methods Surface electromyography was also used to verify the influence of upper body on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 46 publications
(57 reference statements)
2
16
1
Order By: Relevance
“…al. found that the acceleration at initial crank position of 71º was about 35% greater than that with seated position with an initial crank angle of 47º [4]. In evaluating the effect of the initial crank position on cyclist performance, perhaps, it is better to opt for acceleration or speed rather than the power output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. found that the acceleration at initial crank position of 71º was about 35% greater than that with seated position with an initial crank angle of 47º [4]. In evaluating the effect of the initial crank position on cyclist performance, perhaps, it is better to opt for acceleration or speed rather than the power output.…”
Section: Discussionmentioning
confidence: 99%
“…al have studied the effect of initial crank positions on cyclist speed and acceleration in track cycling performance. It was found that the acceleration with standing position and initial crank position of 71° was about 35 % greater than that with seated position with an initial crank angle of 47° [4].…”
Section: Introductionmentioning
confidence: 92%
“…Such delay decreases with increasing initial crank position. According to the results, the optimal initial crank position resulted to be 71° (Padulo et al, 2014)). …”
Section: Discussionmentioning
confidence: 99%
“…Alterations in posture, such as changing from a seated to a standing posture, also result in changes in performance 5,6 . When cycling with a standing posture, a greater production of power output is developed for the same speed, presumably to manage the increased number of degrees of freedom of the lower limbs due to the loss of contact of the buttocks with the saddle 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Surface EMG of the gastrocnemius medialis (GAS), tibialis anterior (TA), erector spinae (at L3 level; ES), and biceps brachii (BB) were recorded at 1500 Hz using pre-amplified bipolar silver-silver chloride (Ag/AgCl) sEMG electrodes. Previous studies have shown that the selected muscles play a major contribution to the production of power during sprint cycling exercises 6,11,18 . The disc electrodes had a diameter of 1 cm and inter-electrode distance of 2 cm.…”
mentioning
confidence: 99%